Yield, Nutrient Content and Uptake by Wheat (Triticum aestivum L) as Influenced by FYM and Sources of Irrigation Water - Aanandi Lal Jat; J.K. Malav (Annals of Arid Zone, 2024)
The multilocation trials were conducted on wheat (Triticum aestivum L.) with farmyard manure (FYM) and sources of irrigation water at farmers’ fields in Sami and Harij talukas of Patan district, North Gujarat Agro-climate Zone of Gujarat during four successive rabi season of 2014-15, 2015-16, 2016-17 and 2017-18. The experiment consisted of two levels of FYM (0 and 10 t FYM ha-1) and three sources of irrigation water viz., sole tube well water, sole canal water and substitute irrigation of tube well and canal water. The trial was arranged in factorial randomized block design with four replications. The results revealed that application of FYM and source of irrigation had a noteworthy consequence on grain and straw yield of wheat on pooled basis. The treatment 10 t FYM ha-1 and alternate application of tube well and canal water resulted in higher grain and straw yield, nitrogen, phosphorus and potassium content and uptake by wheat.